The External Sector Vulnerability Monitoring Index (Λ): The case of Chinese and Asean-5 economies - Mario Arturo Ruiz Estrada; Diwa Samad; Yew Joe Ho (Contemporary Economics, 2018)
This paper introduces an alternative indicator to evaluate the external sector behavior of a country or region. The objective of this indicator, titled 'The External Sector Vulnerability Monitoring Index' (henceforth ESVM) (λ), is to offer policy-makers and researchers a new analytical tool to study the external sector trends and stages of any country from a global perspective. The ESVM-index (λ) is not intended to be a forecasting model. It is focused on showing the past and present economic situation in any country's external sector performance. It can provide a general idea of the situation and evolution of the foreign sector performance of any country. Therefore, the application of the ESVM-index (λ) is based on the characteristics, conditions and historical moments that any country presents in its external sector development. ESVM-index (λ) acts as a simulator that allows the application of a series of different scenarios and phases of external sector performance of any country. In our case, we apply the external sector vulnerability monitoring index (λ) on the Chinese and ASEAN-5 economies.
Keywords: F15; F41; 330; Trade liberalization; Openness; International Trade; ASEAN; China